Web Applications Of Introduction Museum in Jakarta for Elementary School Students Using Html And Macromedia Dreamweaver Mx - Yuni Susilowati (Jurnal Sistem Informasi, 2008)
Currently the development of computer technology, especially the Internet is very dominant in the search for a variety of information required. In this case, a lot of good companies small, medium to large companies that offer berantusias the type of product in this Internet medium. Therefore, following the author participated in information technology development to create a website introduction Museum in Jakarta use the program Macromedia Dreamweaver MX application.